The ecological and evolutionary energetics of hunter-gatherer residential mobility - Hamilton, M; Lobo, J; Rupley, E; Youn, H; West, G (Wiley, 2016)
Residential mobility is a key aspect of hunter-gatherer foraging economies and therefore is an issue of central importance in hunter-gatherer studies.[1-7] Hunter-gatherers vary widely in annual rates of residential mobility. Understanding the sources of this variation has long been of interest to anthropologists and archeologists. The vast majority of hunter-gatherers who are dependent on terrestrial plants and animals move camp multiple times a year because local foraging patches become depleted and food, material, and social resources are heterogeneously distributed through time and space. In some environments, particularly along coasts, where resources are abundant and predictable, hunter-gatherers often become effectively sedentary. But even in these special cases, a central question is how these societies have maintained viable foraging economies while reducing residential mobility to near zero.